Peningkatan Produksi Garam Beryodium Melalui Aplikasi Alat Pencetak Garam Secara Mekanik - Handayani, Dwi; Murni, Murni; Ikhsan, Diyono; Arifan, Fahmi (METANA, 2011)
The salt moulder groups "Muji Rahayu" have a mission for drummed up salt moulders by are very limited, by process technology conventionally. The result of production is salt_powderÂ  which is a gunny_pack then on sale at the prince of low. If it is soled in salt_moulder, the price will increase. Salt moulder form of Instrumentation which it is has incereased quality and sale at the prince salt iodized consumption. However, at the employe moulder machine which is continue, the machine has trouble because it is always related to salt which have a character is corrosive. Therefore, it needs to have a salt_moulder which is simple and easy to be operated by salt-farmer moreover the price is cheap. The salt moulder will work by mechanic and aplication style. Because of the caracter of salt which corrosive, so the contraction which related to salt is made by stainless steel. By the expectation it be able to increase the income of salt_farmers.Â Keywords : iodized salt, salt moulder